DESCRIPTION OF KAZI POSITIONS AND THEIR ACTIVITIES IN THE LOCAL GOVERNMENT SYSTEM - Karimov Kahramon Sadikovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, issues related to the history of Kazakhstani courts, legal regulations, notarial acts, their impact on local government, economic, political, social, religious, cultural life, procedures for conducting business of the Kazakhs of the Turkestan region, legal foundations and legislative reflection of legal values were considered.